UPAYA PENGURANGAN DAN PENANGANAN SAMPAH RUMAH TANGGA DAN SAMPAH SEJENIS RUMAH TANGGA MELALUI KEBIJAKAN STRATEGI DAERAH KOTA BANJARBARU - Manruni, Manruni; Mahyudin, Rizqi Puteri; Achmad, Basir; Mahyudin, Idiannor (EnviroScienteae, 2023)
Banjarbaru City Government seeks to suppress the rising of waste through waste reduction and handling. Based on National Waste Management Information System data for Banjarbaru City in 2022, waste reduction is 24.77% and waste handling is 75.21%, and has not been able to meet Jakstrada's target of 30% reduction and 70% handling. The purpose of this study is to determine the existing conditions for reducing and handling household waste and household-like waste and to analyze the obstacles encountered in efforts to reduce and handle household waste and household-like waste through the Banjarbaru City Regional Policy and Strategy. The existing condition of reducing waste is carried out at 121 waste banks, 1 3R waste disposal site and 2 recycling centers, while waste handling is carried out from 91 waste disposal sites and there are 26 illegal ones. Garbage carrier fleet of 57 units. A total of 145 tons/day of waste is processed at the Gunung Kupang landfill with the controlled landfill system. The results of the analysis of the the main priority AHP method of the waste management model, which is reduction with a weight value of 0.675, while the handling value is 0.325. The results of the priority analysis for the planning component, the first priority aspect on the constraints on managing household waste and household-like waste based on the opinions of respondents is the aspect of Government Policy with a weight value of 0.2690. Then the second priority is public perception (0.2201), the third priority aspect is health (0.2185) the fourth priority is the environment (0.1563) and the fifth priority is financing (0.1361). In the first priority technical component is waste disposal site with a value weight (0.2098), in the second priority is 3R waste disposal site with a value weight (0.2043) in the third priority is recycling center (0.1839) and in the fourth priority is the garbage transport fleet with a weight value (0.1824). The fifth priority is landfill (0.1136) and the sixth priority is the Waste Bank (0.1061).